1985
DOI: 10.1017/s1742758400006512
|View full text |Cite
|
Sign up to set email alerts
|

Life history, development and behaviour ofEldana saccharinaWalker on sugar-cane in southern Ghana

Abstract: Female Eldana saccharina Walker was found to lay 327 ± 17.1 eggs within a period of 4 days and required three surfaces to lay eggs which were mainly deposited on the inner side of leaf sheaths fitting tightly on to the sugar-cane stalk. The mated females laid more eggs per female (327.0 ± 17.1) than virgin females (212.3 ± 5.5). The incubation period of the eggs of E. saccharina was found to be 5.64 ± 0.01 (5–7) days in the laboratory and 5.82 ± 0.03 (5–7) days in the field. The mean larval duration was 31 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…However, Girling (1978) observed in Uganda that stem borer attack was more frequent in the lower than the higher part of the softer varieties, but more frequent in the younger, softer joints near the top than the lower joints in the harder varieties. These and other observations (Sampson and Kumar, 1985) tend to suggest the existence of biotypes of E. saccharina in different geographical areas.…”
Section: Discussionsupporting
confidence: 69%
“…However, Girling (1978) observed in Uganda that stem borer attack was more frequent in the lower than the higher part of the softer varieties, but more frequent in the younger, softer joints near the top than the lower joints in the harder varieties. These and other observations (Sampson and Kumar, 1985) tend to suggest the existence of biotypes of E. saccharina in different geographical areas.…”
Section: Discussionsupporting
confidence: 69%
“…In an earlier study by Dick (1945) females oviposited on average 750 eggs, with a maximum of 1004. Mating increased the number of eggs oviposited compared with unmated females (Dick 1945;Sampson & Kumar 1985). In West Africa, Betbeder-Matibet et al (1977) reported an average fecundity of 460 eggs oviposited per female, up to a maximum of 811 for females reared on an artificial diet.…”
Section: Introductionmentioning
confidence: 99%
“…In a later paper, Betbeder-Matibet (1981) reported similar fecundity but did not state if the females were reared on artificial diet or sugarcane stalks. In East Africa, Waiyaki (1974) reported an average fecundity of 150 to 230 eggs per female and Sampson & Kumar (1985) reported an average fecundity of 327 ± 17 eggs per female reared on sugarcane stalks. Sampson & Kumar (1985) compared adult longevity and life cycle lengths of E. saccharina from Ghana, West Africa with those reported by Girling (1978) from Kenya, East Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Though egg scouts were made throughout the experimental period in the experimental farms, it was only during two occasions in the minor season that ten egg batches were collected. This could be due to the possibility that eggs were laid at spots of the plant where they were difficult to locate as reported by Sampson and Kumar (1985). No egg parasitoids were found probably due to the scanty number of the eggs collected.…”
Section: Resultsmentioning
confidence: 86%